1970
DOI: 10.1139/b70-054
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phytophthora and Pythium species in soils in the Continental United States

Abstract: The Pythium flora of 2132 soil samples from all sections of the United States was determined using an apple trapping method and two selective media. Isolates of the P. irregulare – P. debaryanum complex were obtained from 90% of the samples, and made up 55% of the 10 566 isolates examined. Isolates referable to the P. dissotocum – P. perniciosum complex, P. spinosum, P. splendens, P. ultimum, P. vexans, and heterothallic forms including P. sylvaticum, P. heterothallicum, and P. intermedium were obtained from 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…It is therefore vitally important to develop disease management strategies that include the monitoring of high-temperature Pythium species in recirculating hydroponic culture systems. Pythium and Phytophthora species can be captured in soil using a variety of plant materials as baits (Hendrix and Campbell 1970;Sanchez et al 2000;Thinggaard and Andersen 1995;Watanabe 1981Watanabe , 1984. For example, Thinggaard and Andersen (1995) found that zoospores of Phytophthora cryptogea Pethyb.& Laff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore vitally important to develop disease management strategies that include the monitoring of high-temperature Pythium species in recirculating hydroponic culture systems. Pythium and Phytophthora species can be captured in soil using a variety of plant materials as baits (Hendrix and Campbell 1970;Sanchez et al 2000;Thinggaard and Andersen 1995;Watanabe 1981Watanabe , 1984. For example, Thinggaard and Andersen (1995) found that zoospores of Phytophthora cryptogea Pethyb.& Laff.…”
Section: Discussionmentioning
confidence: 99%
“…Baiting methods have traditionally been used to isolate Pythium and Phytophthora species from soil (Hendrix and Campbell 1970;Matsumoto and Sato 1979;Watanabe 1984). However, there have been few reports on baiting methods to detect zoosporic pathogens in hydroponic solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Pythium spp. fungi, implicated as factors in littleleaf disease (Lorio, 1966;Hendrix and Campbell, 1970), are often associated with P. cinnamomi (Otrosina and Marx, 1975). Armillaria mellea (Vahl) P.…”
Section: Pathogensmentioning
confidence: 99%
“…have been studied with emphasis on their isolations, distribution, and population dynamics in relation to the forest nursery diseases and bean disease complex in the United States and other countries1, 2,3,5,6,7,8) Although considerable knowledge on the seedling diseases of various plants caused by Pythium spp. has recently been accumulated in Japan, only a few reports have been available on their ecology.…”
Section: Introductionmentioning
confidence: 99%